Keypoint based comprehensive copy‐move forgery detection - Diwan, Anjali; Sharma, Rajat; Roy, Anil K.; Mitra, Suman K. (IET image processing, 2021)
Verifying the authenticity of a digital image has been challenging problem. The simplest of the image tampering tricks is the copy‐move forgery. In copy‐move forgery copied portion of the image is pasted on another part of the same image. Geometrical transformations are used on the copied portions of the image before pasting it for the tampered image to look realistic and visually convincing. To make it more complex, other processing approaches may also be applied in the forged region for hiding traces of forgery. These processings are the scale, rotation, JPEG compression, and AWGN. In this paper, an approach based on features of the CenSurE keypoint detector and FREAK descriptor is proposed. This combination has novelty in itself as it has never been used for this purpose before to the best of authors' literature studies. CenSurE detectors are fast and give stable and accurate output even in the case of rotated images, which we club with binary descriptor FREAK. Hierarchical clustering and Neighbourhood search is applied in such a way that it can locate and detect multiple copy‐move forgeries. The authors are hopeful that the proposed approach may be used in real‐time image authentication and copy‐move forgery detection.